Efficient and Rapid Regioselective One‐Pot Synthesis of 1, 4‐Disubstituted 1, 2, 3‐Triazoles from In Situ Generated Potassium Arylethynyltrifluoroborates through Sonogashira Reaction. Issue 28 (29th August 2013) - Song, Jung Ho; Choi, Pilju; Lee, Seung Eon; Jeong, Kyu Hyuk; Kim, Taejung; Kang, Ki Sung; Choi, Yong Soo; Ham, Jungyeob
Abstract: Potassium arylethynyltrifluoroborates, the intermediates generated by the Sonogashira reaction of potassium ethynyltrifluoroborate with various aryl halides, were directly coupled with azides in the presence of a stoichiometric amount of CuI under aqueous conditions, and the desired 1, 4‐disubstituted 1, 2, 3‐triazoles were isolated in good yields. Both electron‐donating and electron‐withdrawing substituents on the potassium arylethynyltrifluoroborates gave moderate to excellent yields of the isolated products. Abstract : A versatile and efficient protocol for the direct one‐pot synthesis of 1, 4‐disubstituted 1, 2, 3‐triazoles from azides and in situ generated potassium arylethynyltrifluoroborate through the Sonogashira reaction of aryl halides with potassium ethynyltrifluoroborate is elaborated.